(untitled) (American Journal of Islam and Society, 2009)
After twenty-seven centuries of uninterrupted presence on the Persian plateau, the Jews of Iran have become so inextricably ingrained in every possible aspect of Iranian life, culture, religion, and history that any valuable work of scholarship in Judeo-Persian studies, such as the one at hand, must by necessity entail an interdisciplinary approach. Between Foreigners and Shi`is, a ground-breaking work that will henceforth prove indispensable to any researcher ofmodern Judeo-Persian studies, is ameticulous piece of scholarship that brings as much novelty to its own field as it does tomodern Iranian historiography, Middle Eastern political studies, and Islamic studies. Daniel Tsadik’s book provides a history of the religious, political, and social life of Iranian Jews under Naser al-Din Shah Qajar (r. 1848-96). Relying on a wealth of previously untapped archival material, the author examines in particular detail episodes of persecution in Barforush in 1866- 67 (pp. 60-78), in Shiraz at the hands of Hajj Sayyid `Ali Akbar Fal Asiri (pp. 130-37), in Isfahan at the hands of ShaykhMohammad Taqi Najafi (pp. 137-49), and in Hamadan at the hands of Mullah `Abdallah (pp. 155-77). Examining these and other episodes of anti-Semitic persecution against the broader backdrop of socio-political events throughout Iran at large, such as the Tobacco Rebellion of 1891 and the great famine, he brings to light a hitherto unnoticed dynamic in which Iran’s Jewish community emerges as the rope in a three-way tug of war between the Shi`ite clergy, the Qajar court, and western diplomats, with each jostling for dominance in the fledgling nation that was becoming modern Iran ...